Design of Wheel Grouser Geometry With Reduced Sinkage for LEV-1 Lunar Rover - Otsuki, Masatsugu; Yoshikawa, Kent; Maeda, Takao; Usami, Naoto; Yoshimitsu, Tetsuo (IEEE robotics and automation letters, 2025)
Surface-mobile platforms have explored the moon and the red planet for nearly half century, providing a wealth of scientific data. However, surface mobility on planetary bodies remains a challenging task. In this letter, the formulation of reaction force by a grouser with a generalized geometry for a wheel of a planetary rover is presented, along with its verification through comparisons with the results by the conventional geometry. In a simulation study, the resistive force theory is applied to a general grouser geometry model. The study determines the impact of several parameters, particularly the grouser inclination, on draw-bar pull. The results obtained from the study suggest the formulation of a design for the grouser that is nearly optimal in its capacity to maximize the draw-bar pull per sinkage. We also apply the proposed geometry to the wheel on LEV-1, demonstrating that it works well in actual lunar operations.